Diabetes and SARS-CoV-2–Is There a Mutual Connection? - Jedrzejak, Anna P.; Urbaniak, Edyta K.; Wasko, Jadwiga A.; Ziojla, Natalia; Borowiak, Malgorzata (Frontiers in Cell and Developmental Biology, 2022)
SARS-CoV-2, a newly emerged virus described for the first time in late 2019, affects multiple organs in humans, including the pancreas. Here, we present the bilateral link between the pathophysiology of diabetes and COVID-19, with diabetes being COVID-19 comorbidity, and a complication of SARS-CoV-2 infection. Analysis of clinical data indicates that patients with chronic conditions like diabetes are at increased risk of severe COVID-19, hospitalization, ICU admission, and death compared to the healthy subjects. Further, we show that SARS-CoV-2 infection might be also associated with the development of new-onset diabetes and diabetic ketoacidosis. We then discuss the options for studying SARS-CoV-2 infection in pancreatic settings, including the use of human pluripotent stem cell-derived pancreatic organoids. Further, we review the presence of SARS-CoV-2 receptors in different pancreatic cell types and the infection efficiency based on pancreatic sections from COVID-19 patients and primary human islet in vitro studies. Finally, we discuss the impact of SARS-CoV-2 infection on human pancreatic cell homeostasis, focusing on β-cells.